2017
DOI: 10.1007/s41105-017-0094-x
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of the ventral tegmental area increased wakefulness in mice

Abstract: The ventral tegmental area (VTA) is crucial for brain functions, such as voluntary movement and cognition; however, the role of VTA in sleep-wake regulation when directly activated or inhibited remains unknown. In this study, we investigated the effects of activation or inhibition of VTA neurons on sleep-wake behavior using the pharmacogenetic “designer receptors exclusively activated by designer drugs (DREADD)” approach. Immunohistochemistry staining was performed to confirm the microinjection sites, and comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Although largely implicated in reward system processing recent evidence suggests that the ventral tegmental area of Tsai (VTA) may also play a role in arousal and cortical activation (Eban-Rothschild et al, 2016;Oishi et al, 2017;Sun et al, 2017;Yu et al, 2019) and defensive responses (Barbano et al, 2020). We found particularly strong fiber labeling here in VTA, one of the strongest BF vGluT2+ projections.…”
Section: Extra-bf Glutamatergic Projections To Arousal-related Brainmentioning
confidence: 49%
“…Although largely implicated in reward system processing recent evidence suggests that the ventral tegmental area of Tsai (VTA) may also play a role in arousal and cortical activation (Eban-Rothschild et al, 2016;Oishi et al, 2017;Sun et al, 2017;Yu et al, 2019) and defensive responses (Barbano et al, 2020). We found particularly strong fiber labeling here in VTA, one of the strongest BF vGluT2+ projections.…”
Section: Extra-bf Glutamatergic Projections To Arousal-related Brainmentioning
confidence: 49%
“…In addition, in the nuclei that connect to PZ GABAergic neurons, BF [37] and BG [38] also regulate NREM sleep. DR dopamine neurons [39], VTA [40] and LH [41] have been reported to regulate wakefulness.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep-Wake Patterns and Arousal. Activation of VTA DAergic neurons by hM3Dq was shown to increase wakefulness periods while reducing sleep-associated behaviors, such as nest building, in both stages of the light/dark cycle in a D 2 R-dependent manner (Oishi et al, 2017a;Sun et al, 2017). Further investigations revealed that NAc D 1 R-and NAc core adenosine A2a receptorexpressing neurons also regulated these sleep-wake patterns (Oishi et al, 2017b;Luo et al, 2018).…”
Section: Modulating Dopamine Signaling and Behavior With Chemogeneticsmentioning
confidence: 98%